(untitled) (Journal of Parents and Teachers, 2012)
Second article from a series of 3 on “Music and Core Competences”. This article presents a proposal based on learning different skills in the classroom with the help of the music. The main objective is the Social and Civic Competence. It focuses on students from Primary Education. The piece of writing is a reflection of the Social and Civic Competence. It also presents two current children’s’ songs and several activities based on those two songs. scuela, editada por PPC. Autor del libro Religión y Música Actual (PPC, 2011), también como músico está presente en el campo de la música religiosa, formando con María Barcea el Grupo CoMpaSIóN, que ya ha publicado los discos “Navidad Actual” editada por PPC. Autor del libro Religión y Música Actual (PPC, 2011), también como músico está presente en el campo de la música religiosa, formando con María Barcea el Grupo CoMpaSIóN, que ya ha publicado los discos “Navidad Actual” (2008) y “Caminamos con Jesús” (2011), además del material musical para el proyecto educativo de Infantil y Primaria “Javerim”, todo ello con la editorial San Pablo.